2020
DOI: 10.3389/fendo.2020.00336
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Diseases and the Risk of Metabolic Syndrome: An Updated Systematic Review and Meta-Analysis

Abstract: Background: Periodontitis and metabolic syndrome (MetS) are two major global health problems that are widely prevalent in the world, although the former is a common infection in developing countries and the latter is a non-infectious but prevalent disease in developed countries. This study aims to provide an updated review on the existence and magnitude of the relationship between periodontal disease and the risk of MetS. Methods: We searched the PubMed, Web of Science, ScienceDirect, Chinese National Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 59 publications
(29 reference statements)
1
34
0
1
Order By: Relevance
“…This highlights a two-way relationship between both pathologies and can be explained by a cause-effect relationship underlined by chronic low-grade inflammation common to periodontal disease and the components of metabolic syndrome we cited above. Inflammatory markers involved in metabolic syndrome (TNF-α, IL-1, IL-6, PAI-1) can upregulate periodontal disease when a persistent periodontal inflammation can exacerbate systemic inflammation, insulin resistance and endothelial dysfunction [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights a two-way relationship between both pathologies and can be explained by a cause-effect relationship underlined by chronic low-grade inflammation common to periodontal disease and the components of metabolic syndrome we cited above. Inflammatory markers involved in metabolic syndrome (TNF-α, IL-1, IL-6, PAI-1) can upregulate periodontal disease when a persistent periodontal inflammation can exacerbate systemic inflammation, insulin resistance and endothelial dysfunction [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis (PD) has also been proposed as a comorbidity associated with MetSyn. Indeed, a meta-analysis revealed a positive association between MetSyn and PD and suggested that individuals with MetSyn are 38% more likely to have PD than individuals without MetSyn [45,46]. Accordingly, Muñoz-Aguilera et al (2020) observed a positive association between hypertension and periodontitis leading to an increase in the risk of high systolic and diastolic blood pressure and hypertension [47].…”
Section: Indicators Related To Associated Diseases/syndromesmentioning
confidence: 99%
“…The most frequent disease leading to death worldwide is a non-communicable disease. Oral health, especially the periodontal condition has been suggested to be affected by noncommunicable diseases [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. An imbalance towards a periodontal immune response is underlined for other chronic diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance towards a periodontal immune response is underlined for other chronic diseases [ 11 ]. Epidemiological studies had shown that periodontitis was associated with the metabolic syndrome [ 3 ] and cardiovascular disease [ 4 , 7 ]. The suboptimal oral function was a potential risk of mortality [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%